2018
DOI: 10.21608/jpp.2018.36631
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability and Heterosis in F1 and F2 Generations of Diallel Crosses among Seven Wheat Genotypes

Abstract: In order to study the effect of heterosis and nature of genetic on plant height and yield traits were studied in a 7x7 diallel cross without reciprocals and their F 2 generation in wheat to define and select an efficient and prospective material for immediate use in hybridization programs to improve grain yield of wheat in Egypt. Parents, F 1 and F 2 were evaluated for quantitative traits in 2016/2017 season. Significant genotype mean squares and its components (parents and crosses) were obtained for all trait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
(10 reference statements)
2
2
0
Order By: Relevance
“…Similarly, the results reported that there were highly significant estimates for both GCA and SCA combining ability effects, indicating the relative importance of additive and non-additive genetic variances for all studied characters. Similar results Zaazaa (2010), and El-Gammaal and Yahya (2018). The ratios of GCA /SCA were more than unity in all studied traits, indicating that additive gene effects were more important than dominance in the expression of these traits.…”
Section: Analysis Of Variancesupporting
confidence: 82%
“…Similarly, the results reported that there were highly significant estimates for both GCA and SCA combining ability effects, indicating the relative importance of additive and non-additive genetic variances for all studied characters. Similar results Zaazaa (2010), and El-Gammaal and Yahya (2018). The ratios of GCA /SCA were more than unity in all studied traits, indicating that additive gene effects were more important than dominance in the expression of these traits.…”
Section: Analysis Of Variancesupporting
confidence: 82%
“…number of spikes per plant, number of grains per spike, spike yield and 1000-grain weight. Significant heterosis was also found by El-Noorka et al (2013), Gammaal andYahya (2018) and Ayoob (2020).…”
Section: Heterosissupporting
confidence: 64%
“…The same conclusion was also drown by Masood and Kornstad (2000), Nazir et al (2005), Al-Hamdany (2010), Ammar et al (2014), Farhat and Darwish (2016), Khilwat et al (2017), El-Gammaal andYahya (2018), Ali et al (2020) and Abro et al (2021…”
Section: Specific Combining Ability (Sca) Effectmentioning
confidence: 61%
“…Plant breeders that work with autogamous crops frequently collect genetic data from diallel cross progenies. Every plant breeding programme must start with insight knowledge regarding the ideal parental mix, focused on a high degree of heterotic response (El-Gammaal and Yahya, 2018). The capacity to combine information also helps geneticists understand the behaviour of the genes responsible for the sign of measurable traits with profitable predominance.…”
mentioning
confidence: 99%